Piperlongumine activates Sirtuin1 and improves cognitive function in a murine model of Alzheimer's disease. (April 2018) - Go, Jun; Ha, Thi-Kim-Quy; Seo, Ji Yeon; Park, Tae-Shin; Ryu, Young-Kyoung; Park, Hye-Yeon; Noh, Jung-Ran; Kim, Yong-Hoon; Hwang, Jung Hwan; Choi, Dong-Hee; Hwang, Dae Youn; Kim, Sanghee; et al.
Highlights: Piperlongumine (PL) activates the deacetylase ability of Sirt1 in vitro . PL improves cognitive deficits in APP/PS1 mice. PL reduces amyloid deposition and neuro-inflammation in the brain of APP/PS1 mice. PL increases VGLUT1 level in the hippocampus of APP/PS1 mice. Abstract: Sirtuin1 (Sirt1) is an unusual target for aging and aging-associated diseases. During the screening for Sirt1 activators from natural compounds, piperlongumine (PL), one of the major constituents of Piper longum, potently activated the deacetylase ability of Sirt1 in vitro . Treatment with PL, which regulated the gene transcription of antioxidant response element in hippocampal neurons, attenuated the cytotoxicity induced by intraneuronal Aβ1-42 expression. The oral administration of PL, at a dose of 50 mg/kg/day for 2.5 months, significantly reduced the occupied area of beta-amyloid in parietal cortex of APP/PS1 mice. Novel object recognition and working memory impairment also markedly improved. Moreover, activated microglia and astrocytes in the cortex notably decreased, indicating the anti-inflammatory activity of PL. Finally, vesicular glutamate transporter 1 significantly increased in the hippocampus of APP/PS1 mice following PL treatment. These results suggested the beneficial effects PL and its therapeutic potential to ameliorate AD-like pathology.